PTEN-Regulated AID Transcription in Germinal Center B Cells Is Essential for the Class-Switch Recombination and IgG Antibody Responses - Wang, Jing; Liu, Sichen; Hou, Baidong; Yang, Meixiang; Dong, Zhongjun; Qi, Hai; Liu, Wanli (Frontiers in Immunology, 2018)
Class-switch recombination (CSR) and somatic hypermutation (SHM) occur during the differentiation of germinal center B cells (GCBs). Activation-induced cytidine deaminase (AID) is responsible for both CSR and SHM in GCBs. Here we show that ablation of PTEN through the Cγ1-Cre mediated recombination significantly influences the CSR and SHM responses. The GCs fail to produce the IgG1 B cells, the high affinity antibodies and nearly lost the dark zone (DZ) in Ptenfl/fl Cγ1Cre/+ mice after immunization, suggesting the impaired GC structure. Further mechanistic investigations show that LPS- and IL-4 stimulation induced the transcription of Cγ1 in IgM-BCR expressing B cells, which efficiently disrupts PTEN transcription, results in the hyper-phosphorylated AKT and FoxO1 and in turn the suppression of AID transcription. Additionally, the reduced transcription of PTEN and AID are also validated by investigating the IgM-BCR expressing GCBs from Ptenfl/fl Cγ1Cre/+ mice upon immunization. In conclusion, PTEN regulated AID transcription in germinal center B cells is essential for the class-switch recombination and IgG antibody responses.